2022
DOI: 10.1021/acs.est.2c00034
|View full text |Cite
|
Sign up to set email alerts
|

Light- and H2O2-Mediated Redox Transformation of Thallium in Acidic Solutions Containing Iron: Kinetics and Mechanistic Insights

Abstract: The redox transformation between the oxidation states of thallium (Tl(I) and Tl(III)) is the key to influencing its toxicity, reactivity, and mobility. Dissolved iron (Fe) is widely distributed in the environment and coexists at a high level with Tl in acidic mine drainages (AMDs). While ultraviolet (UV) light and H 2 O 2 can directly (by inducing Tl(III) reduction) and indirectly (by inducing Fe(III) to form reactive intermediates) impact the redox cycles of Tl in Fe(III)-containing solutions, the kinetics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 85 publications
(180 reference statements)
1
15
0
Order By: Relevance
“…The photochemical reduction of Tl(III) via a LMCT pathway upon irradiation by light has been confirmed in the previous literature. 14,17,58 The nearly linear increase in the firstorder rate constants of Tl(III) reduction with increasing SRFA concentration for all examined pH values (Figure 2c) suggests that LMCT was the dominant pathway for Tl(III) reduction in irradiated SRFA solutions since the concentrations of photoreactive Tl(III) species changed approximately linearly with SRFA concentration (Table S2). To further identify the role of the photogenerated ROS (i.e., H 2 O 2 , O 2…”
Section: Tl(iii)mentioning
confidence: 94%
See 2 more Smart Citations
“…The photochemical reduction of Tl(III) via a LMCT pathway upon irradiation by light has been confirmed in the previous literature. 14,17,58 The nearly linear increase in the firstorder rate constants of Tl(III) reduction with increasing SRFA concentration for all examined pH values (Figure 2c) suggests that LMCT was the dominant pathway for Tl(III) reduction in irradiated SRFA solutions since the concentrations of photoreactive Tl(III) species changed approximately linearly with SRFA concentration (Table S2). To further identify the role of the photogenerated ROS (i.e., H 2 O 2 , O 2…”
Section: Tl(iii)mentioning
confidence: 94%
“…The photochemical reactions are of critical importance for mediating the redox cycling of Tl. , In our earlier study, we showed that the conversion of Tl­(III) to Tl­(I) occurs through a direct charge-transfer process within Tl­(OH) 2+ in acidic solutions upon irradiation via ultraviolet light . The photochemical reduction kinetics of Tl­(III) is highly dependent on solution pH, with a faster reduction rate obtained at higher pH .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, upon these conditions Tl could be released to the water column after reductive dissolution of Fe and Mn oxides, which may sequester significant concentrations of Tl(III) (Nriagu, 1998). However, despite the oxic conditions observed in AMD systems, Tl(I) may predominate due to the high redox potential of the Tl(III)/Tl(I) couple (Casiot et al, 2011) and also probably due to the UV-mediated reduction of Tl(III) to Tl(I) in acidic Fe(III)-rich solutions (Ma et al, 2022). Different works have dealt with the mobility and transport of Tl in AMD affected water courses.…”
Section: Thallium Transport In Acidic Water Coursesmentioning
confidence: 99%
“…Campanella et al (2018) studied the distribution of aqueous Tl(I)/Tl(III) in an abandoned mining area of Valdicastello Carducci (Italy) as a function of light exposure and solution properties and composition. Ma et al (2022) discussed the redox transformation of thallium in acidic solutions containing iron, concluding that UV light and H 2 O 2 could directly reduce Tl(III) to Tl(I), with the extent of reduction dependent on the presence of Fe(III) and the solution pH, and therefore expanding our current understanding of geochemical Tl redox cycling and its implications for evaluating the ability of Fe to induce oxidation state changes in Tl species in the aquatic environment. Casiot et al (2011) reported Tl concentrations of up to 534 μg/L in a river impacted by AMD downstream from the abandoned Carnoulès Mine (France) and its sorption on Fe hydroxides.…”
Section: Introductionmentioning
confidence: 99%